2021
DOI: 10.1080/0886022x.2021.2009863
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram for predicting acute kidney injury after orthotopic liver transplantation

Abstract: Background We aim to develop and validate a nomogram model for predicting severe acute kidney injury (AKI) after orthotopic liver transplantation (OLT). Methods A total of 576 patients who received OLT in our center were enrolled. They were assigned to the development and validation cohort according to the time of inclusion. Univariable and multivariable logistic regression using the forward variable selection routine were applied to find risk factors for post-OLT sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
4
1
Order By: Relevance
“…In the current study, we noted that AKI is a common issue for LT patients. According to the 2012 KDIGO criteria, we observed that the incidence of post-LT AKI in our center was 37.2%, which is slightly lower than the 40%–60% reported previously ( 4 , 5 , 7 , 8 ). However, compared with the other surgical population (e.g., orthopedic and gastrointestinal surgery), which was reported to vary from 2.9% to 11.8%, LT patients have a much higher postoperative AKI incidence.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…In the current study, we noted that AKI is a common issue for LT patients. According to the 2012 KDIGO criteria, we observed that the incidence of post-LT AKI in our center was 37.2%, which is slightly lower than the 40%–60% reported previously ( 4 , 5 , 7 , 8 ). However, compared with the other surgical population (e.g., orthopedic and gastrointestinal surgery), which was reported to vary from 2.9% to 11.8%, LT patients have a much higher postoperative AKI incidence.…”
Section: Discussioncontrasting
confidence: 71%
“…Many studies have demonstrated that several intraoperative factors can significantly contribute to postoperative AKI ( 14 ), and electrolyte/acid-base balance disorder, hypotension, blood or FFP transfusion, lactate concentration and urine output have been associated with an increased incidence of AKI. ( 4 , 5 , 7 , 8 ) As we expected, two intraoperative risk factors (insulin dosage and anhepatic phase urine volume) were identified as independent predictors in this study. Regarding such intraoperative factors, clinicians can modify our intraoperative care and improve surgical procedures to reduce the risk of postoperative AKI.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…According to studies, the prevalence of CKD is higher in people ≥65 years than in younger age group, and other risk factors for CKD such as heart disease, obesity, and previous kidney injury are also more common in older adults [ 40 ]. Patients with high BMI have more severe oxidative stress and endothelial dysfunction, and are less able to cope with stress renal hypoperfusion during surgery [ 41 ]. Family history of kidney disease shows varying effects on disease progression among people of different races and regions, which are closely related to social, economic, educational, and other factors [ 42 ].…”
Section: Discussionmentioning
confidence: 99%